Evaluation of reactive power support in solar PV prosumer grid - Peprah, Forson; Gyamfi, Samuel; Effah-Donyina, Eric; Amo-Boateng, Mark (e-Prime, 2022)
Electricity prosumption is gaining ground due to price reduction in solar PV systems. The presence of prosumers on the low voltage grid is said to compromise power quality in the grid. Many researchers have reported over-voltage and high power loss in the prosumer grid. Power utility regulators ensure that operators work within voltage and power loss benchmarks. To meet voltage and power loss benchmarks, operators use tap changers, capacitor banks, and static volt-ampere-reaction (VAr) compensators. Finding the optimal placement of such compensators on the low voltage prosumer grid to minimise voltage deviation and line loss is always a problem. Their allocation is not a trivial task when the objective is to provide a comprehensive benefit to the power system. This paper aims to analyse the suitability of using reactive power support (RPS) and solar photovoltaics to achieve active voltage management, minimise power loss, and reduce transformer capacity in prosumer grids PV using the python optimisation algorithm. The results show that solar photovoltaic injection and reactive power compensation positively and negatively impact the prosumer grid. Operating the grid with PV and RPS injections with specific transformers capacities does not create over-voltage and high-power loss problems. The results obtained from the scenarios show that operating the grid as a consumer grid has high power loss than operating it with PV injection and RPS.